2014
DOI: 10.1186/1471-2334-14-25
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genetic characterization of Cryptosporidium, Enterocytozoon, Giardia and Cyclospora in diarrheal outpatients in china

Abstract: BackgroundCryptosporidium spp., Enterocytozoon spp., Giardia spp. and Cyclospora spp. are important intestinal protozoan parasites causing diarrhea in humans, livestocks and wildlife and have a significant impact on public health. No reports exist about simultaneous prevalence rates or genotyping data of these four parasites in outpatients from China.MethodsFecal specimens from 252 diarrhea patients in a pediatric clinic (n = 169) and an intestinal clinic (n = 83) of a hospital in Shanghai, China, were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
99
5
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 49 publications
7
99
5
2
Order By: Relevance
“…This is in accordance with previously published reports worldwide [2,20,[27][28][29][30]. Conversely, in a study from India, E. intestinalis has been detected as the most common cause of infection among HIV-infected patients with diarrhea [5].…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with previously published reports worldwide [2,20,[27][28][29][30]. Conversely, in a study from India, E. intestinalis has been detected as the most common cause of infection among HIV-infected patients with diarrhea [5].…”
Section: Discussionsupporting
confidence: 92%
“…In tropical countries, the highest prevalence of Cryptosporidium infection is usually associated with the rainy season, and water-borne transmission is considered a major route in these areas (Ajjampur et al 2010). On the other hand, Liu et al (2014) reported higher infection rates in winter than in spring in Shanghai, China.…”
Section: Discussionmentioning
confidence: 92%
“…C. andersoni is a gastric parasite which has been associated with reduced milk yield in dairy cattle and decreased weight gain in post weaned calves (Olson et al 2004) and is occasionally detected in humans (Leoni et al, 2006;Morse et al, 2007;Waldron et al, 2011;Agholi et al, 2013;Jiang et al, 2014;Liu et al, 2014). Two studies in China by the same research group have reported that C. andersoni was the most prevalent Cryptosporidium species detected in humans Liu et al, 2014). However, further research is required to better understand the zoonotic importance of C. andersoni and it has not been identified in humans in Jordan in the one previous genotyping study (Hijjawi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%